The contemporary British novel - Acheson, James, 1947-; Ross, Sarah C. E. (Edinburgh University Press, 2005)
Written by some of the world's finest contemporary literature specialists, the specially commissioned essays in this volume examine the work of more than twenty major British novelists. Focusing largely on authors whose first novels have appeared since 1980, the essays provide expert and original analysis of the most recent trends in the theory and practice of contemporary British fiction. This book will be of interest not only to students, teachers and lecturers, but to the general reader seeking help in approaching the often baffling novels of the recent past.